PERTANGGUNGJAWABAN KANTOR PERTANAHAN ATAS PENERBITAN SERTIPIKAT GANDA BAGI PEMEGANG HAK MILIK ATAS TANAH (STUDI KASUS PUTUSAN NOMOR 31/G/2022/PTUN.SMG) - Haerudin; Dilla Hariyanti (Constitutum: Jurnal Ilmiah Hukum, 2024)
Land Registration aims to provide legal certainty and protection to land rights holders. However, in practice, it is not uncommon for two or more land certificates to be issued by the land office for the same plot of land. The cause of double certificates, according to Decision Number 31/G/2022/PTUN.SMG is due to changes in spatial planning by the district government and human error, where land that has already been certified by the National Land Agency (BPN) undergoes spatial planning changes. Additionally, land office officials do not conduct thorough investigations. The responsibility of the land office for the issuance of double certificates is to be fully accountable for resolving legal issues/disputes arising from double certificates, which cause losses to landowners. This responsibility includes complying with court decisions that require the land office to revoke and remove the certificate from the land register, and to pay the legal costs of the double certificate dispute. According to the provisions of Article 7 paragraph (2) letter l of Law Number 30 of 2014 concerning Government Administration, government officials are obligated to comply with court decisions that have permanent legal force.